2010
DOI: 10.3928/1081597x-20091030-01
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Corneal Elasticity Coefficient Using the ORA Database

Abstract: The elasticity coefficient calculated using the ORA applanation curve can be used in the evaluation of corneal biomechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…Avetisov et al developed an elasticity coefficient from the ORA applanation curve that describes velocity change occurring at the end of applanation. 28 Touboul et al proposed a variable (CH-CRF) expressing the difference between CH and CRF that was greater in KC and post-LASIK corneas while rare in normal and glaucoma study groups. 20 Schweitzer et al investigated some aspects of the infrared signal (peak amplitude 1, peak amplitude 2, width of peak 1 at half the maximum value, and width of peak 2 at half the maximum value) and air pressure curve (P1, P2, Pmax and time at these points) and found that all but the width of peak 2 at half the maximum value were significantly lower in KC when compared to CCT-matched healthy corneas; however, significant overlap existed for the variables.…”
Section: Discussionmentioning
confidence: 99%
“…Avetisov et al developed an elasticity coefficient from the ORA applanation curve that describes velocity change occurring at the end of applanation. 28 Touboul et al proposed a variable (CH-CRF) expressing the difference between CH and CRF that was greater in KC and post-LASIK corneas while rare in normal and glaucoma study groups. 20 Schweitzer et al investigated some aspects of the infrared signal (peak amplitude 1, peak amplitude 2, width of peak 1 at half the maximum value, and width of peak 2 at half the maximum value) and air pressure curve (P1, P2, Pmax and time at these points) and found that all but the width of peak 2 at half the maximum value were significantly lower in KC when compared to CCT-matched healthy corneas; however, significant overlap existed for the variables.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies in the literature analyzing aspects of the Ocular Response Analyzer corneal deformation signal waveform other than CH and CRF. 12,13 The clinical significance of these various waveform parameters is currently unknown. The purpose of our study was to identify which of the new parameters could differentiate post-femtosecond LASIK corneas from those with manifest keratoconus after controlling for potential confounding factors such as CCT and age.…”
Section: Discussionmentioning
confidence: 99%
“…Although a low CH (<8 mm Hg) might be a predictive index of a preectatic conditions [3, 33], the overlap in the distribution of both CH and CRF values within the normal population does not support a role for CH and CRF measurement as single predictors to detect early ectasia or to predict its onset before surgery [91]. Instead, waveform analysis of ORA signals [33, 82, 92] has shown that the morphology of the signal may provide additional information. For instance, in a case of iatrogenic ectasia after LASIK, Kerautret et al [33] found a lower Peak 1 height in the ectatic eye than in the fellow nonectatic eye, despite the similar CH and CRF values in the 2 eyes.…”
Section: Factors Affecting Corneal Biomechanical Propertiesmentioning
confidence: 99%